Fully Printed Electrodes on Stretchable Textiles for Long‐Term Electrophysiology. Issue 4 (20th February 2017) - Bihar, Eloïse; Roberts, Timothée; Ismailova, Esma; Saadaoui, Mohamed; Isik, Mehmet; Sanchez‐Sanchez, Ana; Mecerreyes, David; Hervé, Thierry; De Graaf, Jozina B.; Malliaras, George G.
Abstract : Fully printed electrodes consisting of a conducting polymer and an ionic liquid gel are fabricated on a stretchable textile. They are shown to record cardiac activity while the wearer is moving and for long periods of time, paving the way for the development of low‐cost devices for continuous health monitoring. Abstract : Fully printed electrodes consisting of a conducting polymer and an ionic liquid gel are fabricated on a stretchable textile. They are shown to record cardiac activity while the wearer is moving and for long periods of time, paving the way for the development of low‐cost devices for continuous health monitoring.